Mulch amendment facilitates early revegetation development on an abandoned field In northern mixed grass prairies of North America - Mollard, Federico Pedro Otto (2016)
Extensive areas of the northern mixed grass prairies of North America require restoration and reclamation as they have been extensively disturbed by agricultural, mining and oil and gas related activities. Amending seedbeds with mulch may avoid soil erosion and help both plant recruitment and early vegetation development in these water limited landscapes. A field experiment was established to determine if straw and hay mulch facilitate early revegetation. The site is an abandoned irrigation area in southern Alberta, Canada. Soil was tilled and the seedbed prepared through manual harrowing, then plots were broadcast seeded with Elymus trachycaulus, Bouteloua gracilis, Astragalus canadensis and Linum lewisii. Hay and straw mulch were applied at two rates (300 and 600 g m−2). Plant recruitment and cover were assessed through the first four years. Mulch had a positive impact on recruitment of all species planted except Bouteloua gracilis. While a thinner material like hay proved to be most effective at high rates (600 g m−2), a thicker material like straw encouraged quick recruitment for these species only at low application rates (300 g m−2). However, these early differences among mulch treatments did not show an impact in either recruitment or cover during subsequent years. Bouteloua gracilis, whose recruitment and growth were broadly impaired by mulch, showed an abundant and constantly increasing cover in the bare ground control and in plots with low application rates of hay. Both recruitment and cover per species indicate that plots are following two different trajectories that show some degree of resilience; the bare ground treatment is dominated by Bouteloua gracilis whereas the mulch treatments are characterized by vegetation dominated by Elymus trachycaulus, Linum lewisii and Astragalus canadensis.